Comparative In Vitro Activities of Amoxicillin-Clavulanate against Aerobic and Anaerobic Bacteria Isolated from Antral Puncture Specimens from Patients with Sinusitis - Goldstein, Ellie J. C. (American Society for Microbiology, 1999)
By an agar dilution method, the antimicrobial susceptibilities of antral sinus puncture isolates were studied. Pneumococci were generally susceptible to amoxicillin, azithromycin, and clarithromycin, but 17% of pneumococcal isolates were resistant to cefuroxime. Haemophilus influenzae isolates were resistant to amoxicillin and clarithromycin. β-Lactamase production occurred in 69% of Prevotella species. One-third of Peptostreptococcus magnus isolates were resistant to azithromycin and clarithromycin. Cefuroxime had limited activity against Prevotella species and P. magnus. Levofloxacin was active against most isolates except peptostreptococci. Amoxicillin-clavulanate was active against all isolates, with the MIC at which 90% of the isolates were inhibited being ≤1 μg/ml.